Commentary on alignment of medical student assessment and vocational training in psychiatry and addiction medicine. (April 2023) - Looi, Jeffrey CL; Bonner, Daniel; Maguire, Paul A; Brazel, Matthew; Keightley, Philip; Reay, Rebecca E; Tedeschi, Michael
Objective: To comment upon the potential for alignment of medical student assessment and vocational specialist training through the RANZCP-CanMEDS model of Entrustable Professional Activities (EPAs) and Workplace-Based Assessments (WBAs). We discuss a specific post hoc example of such an alignment in an Australian graduate medical school in Psychiatry and Addiction Medicine. Conclusions: Vocational training models of assessment, such as the RANZCP specialist training program for psychiatrists, can potentially be mapped to medical student education in formative and summative assessment through CanMEDs-based EPAs and WBAs, to assist in transition to specialist training.